Zachowania agresywne i autodestruktywne a ich wpływ na postrzeganie siebie przez adolescentów = Influence of aggressive behaviour and autoaggressive behaviour on adolescences - Trepka-Starosta, Justyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This article presents destructive behavioral, by which is meant the agressive and autoaggressive behaviour in indirect and direct forms. A particular object of the research was study the potential differences in self-image presented by the aggressive and self-injurious adolescent induviduals. The study also addressed the issue of examining the thesis that aggression and selfaggression are mutually exclusive.
Keywords: agresja; autodestrukcja; zachowania agresywne; zachowania autodestruktywne; samoocena; obraz siebie; aggression; autoaggression; aggressive behaviour; autoaggressive behaviour; self-image